How healthy will be the air quality in 2050? - Monteiro, A. (2018)
The air quality standards defined by the World Health Organization (WHO), and updated in 2005, continue to be much more exigent than current EU legislation, namely regarding the most critical pollutants over Europe: ozone (O3) and particulate matter (PM10 and PM2.5). This work intends to evaluate the fulfilment of these WHO standards in the present and in the future, including climate change effects. This study will be focused on Portugal, where each year, the O3 and PM10 concentrations exceed the legislated limit values. For this, regional air quality simulations for present and future periods were conducted, with CAMx version 6.0, to investigate the impacts of climate change and anthropogenic emission projections on air quality over Portugal in 2050. The climate and emission projections for 2050 were derived from the Representative Concentrations Pathway 8.5 scenario. Modelling results show that, over Portugal, the WHO standards are already not being fulfilled and will continue to be surpassed in the future. When considering climate change and projected anthropogenic emissions and comparing them to the actual scenario, a reduction in the maximum 8-h daily O3 concentration is expected. For PM, the results indicate serious problems regarding the health impact expected for both long-term and short-term exposure. The annual averages for both PM10 and PM2.5 exceed the AQG over the country. The PM short-term exposure is already very high for current conditions and higher impacts are expected for future scenario, in particular regarding the PM10 values. This air quality degradation is caused by the warmer and dryer conditions and the increase of background concentrations of pollutants expected for the 2050 climate. The results evidence that human health protection will be even more critical in the future, particularly for particulate matter. Furthermore, urgent air quality management strategies need to be designed, with transboundary cooperation and implementation.